SimplySiti / Nur Alissa Irwani Norirwan - Norirwan, Nur Alissa Irwani (2021)
Overall, this contextual investigation is about the foundation of Dato Siti Nurhaliza binti Tarudin. She is the founder of her product “SimplySiti”. She is a Malaysian singer, songwriter, actress and businesswoman with more than 300 local and international awards. She had launched her own beauty product line (SimplySiti) in 2010 which had made nationwide sensation in both local and the international market. With the help of her husband, Datuk Seri Khalid Mohd Jiwa and two others business partners, she ventured into the cosmetic industry after two years of research with AC Nielsen to study the market and target customers. The brand's name was derived from the word “simplicity”. For this situation study, I might want to share about the business person and a couple of things that everybody must know about Dato Siti Nurhaliza and her product's. There are many difficulties that Dato Siti Nurhaliza needs to look before her successful in business. Last but not least, everyone should makes Dato Siti Nurhaliza as their own roll model because she is a good business person in Malaysia. SimplySiti of this case study is that we are able to see the situation where we see the existence problem that needs to be solved. After i have do investigation, I had found that the model of the business is manufacturing. With the inclusion of nanotechnology, cosmetics are manufactured in Korea. The nature of this business is health and beauty. SimplySiti is creating a premium local brand that able to position itself at par with the international brands. The primary marketing objective is to establish SimplySiti as the best Asian brand in cosmetic. My references of this case study is from internet. I using my internet to access more knowledge about SimplySiti. The entrepreneur must have the features to make the entrepreneurs more competitive and sustainable and it allows an entrepreneur to get competition advantage when compared with other entrepreneurs. After I have studied about this product, I think this product is a good and can be more success in the future. After that, after studied about this, I know more knowledge about the materials that have in SimplySiti.